Hadith #816 - Bulugh al-Maram (Bulugh al-Maram)
Abu Hurairah (RAA) narrated that the Messenger of Allah said, “The performance of ‘Umrah is an expiation for all the sins committed (between this ‘Umrah and the previous one), and the reward for Hajj Mabrur (the one accepted by Allah or the one which was performed without doing any wrong) is nothing save Paradise.” Agreed upon.
Grade:

Hadith #817 - Bulugh al-Maram (Bulugh al-Maram)
Hajj and ‘Umrah.” Related by Ahmad and Ibn Majah and the wording is his. It is reported with a sound chain of narrators.
Grade:

Hadith #818 - Bulugh al-Maram (Bulugh al-Maram)
Jabir bin ‘Abdullah (RAA) narrated, A Bedouin came to the Prophet (ﷺ) and said, ‘O Messenger of Allah! Tell me about ‘Umrah! Is it compulsory? He replied (ﷺ), “No (it is not compulsory), but it is better for you to perform it.” Related by Ahmad and at-Tirmidhi. Scholars are of the opinion that it is Mawquf.
Grade:

Hadith #819 - Bulugh al-Maram (Bulugh al-Maram)
Ibn ‘Adi narrated with a weak chain of narrators on the authority of Jabir (RAA) in a Hadith Marfu’ (connected to the Prophet (ﷺ), “Hajj and ‘Umrah are compulsory.”
Grade:

Hadith #820 - Bulugh al-Maram (Bulugh al-Maram)
Anas (RAA) narrated that the Messenger of Allah (ﷺ) was asked, ‘What is as-Sabil?’ The Messenger of Allah (ﷺ) replied, “Provision of food and means to make the journey.” Related by Ad-Daraqutni and rendered authentic by Al-Hakim.
Grade:

Hadith #821 - Bulugh al-Maram (Bulugh al-Maram)
At-Tirmidhi reported the same hadith on the authority of Ibn ’Umar but with a weak chain of narrators.
Grade:

Hadith #822 - Bulugh al-Maram (Bulugh al-Maram)
Ibn ’Abbas (RAA) narrated, The Messenger of Allah (ﷺ) came across some riders at ar-Rauha’ (a place near Madinah). He asked them, “Who are you?” They replied, ‘Who are you?’ He replied, “I am the Messenger of Allah.” A woman then lifted up a boy, and asked the Prophet, Will this boy be rewarded for Hajj? The Messenger of Allah (ﷺ) replied, “Yes, and you too will be Rewarded.” Related by Muslim.
Grade:

Hadith #823 - Bulugh al-Maram (Bulugh al-Maram)
lbn ’Abbas (RAA) narrated that ‘Al-Fadl Ibn ’Abbas was riding behind the Messenger of Allah (ﷺ) when a woman from the tribe of Khath‘am came along, and al-Fadl started looking at her and she also started looking at him. The Messenger of Allah (ﷺ) kept on turning al-Fadl’s face to the other side. She said, ‘O Messenger of Allah! Allah has prescribed Hajj for His servants, and it has become due on my father who is an old man, who cannot sit stable on his mount. Shall I perform Hajj
Grade:

Hadith #824 - Bulugh al-Maram (Bulugh al-Maram)
“Yes perform Hajj on her behalf. Had there been a debt on your mother, would you have paid it or not? So, pay off her debt to Allah, for He is most deserving of settlement of His debt.” Related by Al-Bukhari.
Grade:

Hadith #825 - Bulugh al-Maram (Bulugh al-Maram)
“Any minor (child) who performs Hajj must perform it again after coming of age; any slave who performs Hajj and is then freed, must perform his Hajj again.” Reported by lbn Shaibah and Al-Baihaqi. lts narrators are authoritative but scholars say that it is Mawquf.
Grade:

Hadith #826 - Bulugh al-Maram (Bulugh al-Maram)
Ibn ‘Abbas (RAA) narrated, ‘I heard the Messenger of Allah (ﷺ) saying, “A man must never be alone with a woman unless there is a Mahram with her. A woman also may not travel with anyone except with a Mahram (relative).” A man stood up and asked, ‘O Messenger of Allah! My wife has gone for Hajj while I am enlisted for such and such a battle, what should I do?’ The Messenger of Allah (ﷺ) replied, “Go and join your wife in Hajj.” Agreed upon, and the wording is from Muslim.
Grade:

Hadith #827 - Bulugh al-Maram (Bulugh al-Maram)
Ibn ‘Abbas (RAA) narrated, The Messenger of Allah (ﷺ) heard a man saying, ‘O Allah! Here I am in response to Your call (saying Labbayk on behalf.. ) on behalf of Shubrumah.’ The Messenger of Allah (ﷺ) asked him. “Have you performed your own Hajj?” He replied, ‘No,’ whereupon the Prophet told him, “You must perform Hajj on your own behalf first, and then perform it on behalf of Shubrumah.” Related by Abu Dawud and Ibn Majah. Ibn Hibban graded it as Sahih.
Grade:

Hadith #828 - Bulugh al-Maram (Bulugh al-Maram)
“Had I said ‘yes’, it would have become a (yearly) obligation. Hajj is obligatory only once in one’s lifetime. Whatever one does over and above this is supererogatory (a voluntary act) for him.” Related by the five Imams except for at-Tirmidhi.
Grade:

Hadith #829 - Bulugh al-Maram (Bulugh al-Maram)
A similar narration was also related by Muslim on the authority of Abu Hurairah.
Grade:

Hadith #830 - Bulugh al-Maram (Bulugh al-Maram)
Ibn ‘Abbas (RAA) narrated that the Messenger of Allah (ﷺ) specified for the people of Madinah, DhulHulaifah (a place 540 km to the north of Makkah) as miqat. For those coming from ash-Sham (including Syria, Jordan and Palestine), he specified al-Juhfah (a place 187 km to the north-west of Makkah and close to Rabigh, where they now perform their Ihram). For those coming from Najd, he specified Qran al-Manazil, (a mountain, 94 km to the east of Makkah, overlooking ‘Arafah. For those coming f
Grade:

Hadith #831 - Bulugh al-Maram (Bulugh al-Maram)
A’ishah (RAA) narrated’ ‘The Messenger of Allah (ﷺ)specified for those coming from Iraq, Dhat ‘Irq (a place 94 km to the north-east of Makkah) as their Miqat.’ Related by Abu Dawud and An-Nasa’i`.
Grade:

Hadith #832 - Bulugh al-Maram (Bulugh al-Maram)
Muslim related a similar narration on the authority of Jabir, but it is most probably Mawquf.
Grade:

Hadith #833 - Bulugh al-Maram (Bulugh al-Maram)
Al-Bukhari reported that it was Umar, who specified Dhat ‘Irq as the miqat (of those coming from Iraq).
Grade:

Hadith #834 - Bulugh al-Maram (Bulugh al-Maram)
Ibn ’Abbas narrated that the Messenger of Allah (ﷺ) specified al-Aqiq (a part of `Dhat Irq) for those coming from the east.’ Related by Ahmad, Abu Dawud and An-Nasa’i.
Grade:

Hadith #835 - Bulugh al-Maram (Bulugh al-Maram)
A’isha (RAA) narrated, ‘We left Madinah with the Messenger of Allah (ﷺ) to perform the Farewell Hajj. Some of us declared Ihram to perform ‘Umrah, while others declared their intentions to perform both Hajj and ‘Umrah. Yet others declared their lhram to perform Hajj only. The Prophet (ﷺ) declared Ihram for Hajj only. Those who intended ‘Umrah terminated their Ihram as soon as they finished the rituals of ‘Umrah. Those who intended to perform Hajj only or to combine Hajj with ‘U
Grade:

Hadith #836 - Bulugh al-Maram (Bulugh al-Maram)
Ibn ‘Umar (RAA) narrated, ‘The Messenger of Allah (ﷺ) used to start saying the Talbiyah. (after entering the state of Ihram) from the mosque of Dhul Hulaifa (i.e. from the Miqat of Madinah). Agreed upon.
Grade:

Hadith #837 - Bulugh al-Maram (Bulugh al-Maram)
“Jibril (peace be upon him) came to me and told me: ‘Command your Companions to raise their voices when saying Talbiyah.” Related by the five Imams and rendered authentic by At-Tirmidhi and Ibn Hibban.
Grade:

Hadith #838 - Bulugh al-Maram (Bulugh al-Maram)
Zaid bin Thabit (RAA) narrated, ‘When the Messenger of Allah (ﷺ) intended to make Ihram for Hajj, he would wash, and take off his ordinary clothes (and put on his white Ihram).” Related by At-Tirmidhi who declared it to be Hadith-Hasan.
Grade:

Hadith #839 - Bulugh al-Maram (Bulugh al-Maram)
Ibn ‘Umar (RAA) narrated, ‘The Messenger of Allah (ﷺ) was asked about what the person who is in a state of Ihram (Muhrim) should wear. He answered, “A person in the state of Ihram. is not allowed to wear a sewn shirt, a turban, trousers, a hooded robe, shoes or sewn slippers (Khuff), unless one is unable to find unsown slippers, then he may wear his Khuff or shoes provided one cuts them below the ankles, and you must not wear clothing that has been dyed with sweet smelling fragrance (suc
Grade:

Hadith #840 - Bulugh al-Maram (Bulugh al-Maram)
A’ishah (RAA) narrated, ‘I used to apply perfume to the Prophet (ﷺ) when he intended to enter the state of Ihram, before he put on his Ihram (garments). And again when he ended his state of Ihram, but before he had made Tawaf around the Ka’bah.’ Agreed upon.
Grade:

Hadith #841 - Bulugh al-Maram (Bulugh al-Maram)
“A Muhrim (one in the state of Ihram) must not contract marriage, nor help others contract marriage, nor get engaged to marry.” Related by Muslim.
Grade:

Hadith #842 - Bulugh al-Maram (Bulugh al-Maram)
Abu Qatadah Al-Ansari (RAA) narrated concerning his hunting a zebra while he is not in a state of Ihram, that ‘Allah’s Messenger (ﷺ) said to Abu Qatada’s companions -who were in a state of Ihram, “Did any one of you ask Abu Qatadah to attack the herd, or point it out to him?” They said, ‘No.’ The Prophet then said, “Then, you may eat what is left of the quarry.” Agreed upon.
Grade:

Hadith #843 - Bulugh al-Maram (Bulugh al-Maram)
As-Sa’b bin Jath-thamah al-Laithi (RAA) narrated, ‘He presented to the Prophet (ﷺ) the meat of a zebra while he was in the area known as al-Abwa’ or Waddan. The Prophet (ﷺ) declined it, and said to him, “We declined your present only because we are in the state of Ihram.” Agreed upon.
Grade:

Hadith #844 - Bulugh al-Maram (Bulugh al-Maram)
“Five kinds of animals are vicious and harmful, and they may be killed outside or inside the sacred area of Ihram (Sanctuary). These are: the scorpion, the kite, the crow, the mouse, and the rabid dog.” Agreed upon.
Grade:

Hadith #845 - Bulugh al-Maram (Bulugh al-Maram)
Ibn ‘Abbas (RAA) narrated, ‘The Messenger of Allah (ﷺ) had himself cupped while he was in the state of Ihram Agreed upon.
Grade:

Hadith #846 - Bulugh al-Maram (Bulugh al-Maram)
Ka’b bin ‘Ujrah (RAA) narrated, ‘I was carried to the Prophet (ﷺ) and the lice were falling over my face. He said, “I did not know that your disease is hurting you as much as what I see. Can you sacrifice a sheep?” I said, ‘No.’ He then said. “Fast for three days or feed six poor people, half a Sa’ each.” Agreed upon.
Grade:

Hadith #847 - Bulugh al-Maram (Bulugh al-Maram)
Abu Hurairah (RAA) narrated, ‘When Allah, the Most High granted His Messenger (ﷺ) victory on the conquest of Makkah, the Prophet (ﷺ) addressed the people, so he glorified Allah and praised Him, and said, “Allah withheld the elephant from Makkah and empowered His Messenger and the believers over it. It has not been made lawful (i.e. fighting in it) for anyone before me, but it has been lawful for me only for a few hours on that day (of the conquest), and it will not be made lawful to anyo
Grade:

Hadith #848 - Bulugh al-Maram (Bulugh al-Maram)
‘Abdullah bin Zaid bin ’Asim (RAA) narrated that the Messenger of Allah said, “Ibrahim declared Makkah as a Haram (Sanctuary) and made supplication for its people, and I declare Madinah to be a Haram just as Ibrahim declared Makkah as a Haram, and I made supplication for its Mudd and Sa’ (refer to hadith no. 650), just as Ibrahim made supplication for the people of Makkah.” Agreed upon.
Grade:

Hadith #849 - Bulugh al-Maram (Bulugh al-Maram)
“Madinah is a Haram (Sanctuary) and its Sacred Precincts extend from ’Air to Thawr (the names of two mountains).” Related by Muslim.
Grade:

Hadith #850 - Bulugh al-Maram (Bulugh al-Maram)
“Labbaika Allahumma labbaik labbaika la sharika laka labbaik, innal hamda wan-ni’mata laka wal mulk, la sharika lak (O Allah! I hasten to You. You have no partner. I hasten to You. All praise and grace is Yours and all Sovereignty too; You have no partner). When we came with him to the House (of Allah), he placed his hands on the Black Stone (Hajar al Aswad) and kis+sed it. He then started to make seven circuits (round the Ka’bah), doing ramal (trotting) in three of them and walking (at hi
Grade:

Hadith #851 - Bulugh al-Maram (Bulugh al-Maram)
Khuzaimah bin Thabit (RAA) narrated, ‘When the Messenger of Allah (ﷺ) finished his Talbiyah whether in Hajj or ‘Umrah, he would ask Allah for His good pleasure and acceptance and ask Him for Paradise, and would seek refuge in Him from Hell.’ Related by Ash-Shafi’i with a weak chain of narrators.
Grade:

Hadith #852 - Bulugh al-Maram (Bulugh al-Maram)
“I have offered my sacrifice here (at Mina) and all of Mina is a place for slaughtering, so sacrifice where you are staying (at Mina). And I have stopped here (at Arafat) and all of Arafat is a stopping place (for the Day of Arafat on the 9th of Dhul-Hijjah). And I have stood here, and all of Jam’ (meaning al·Muzdalifah) is a place for standing.” Related by Muslim.
Grade:

Hadith #853 - Bulugh al-Maram (Bulugh al-Maram)
A’ishah (RAA) narrated, ‘When the Messenger of Allah (ﷺ) came to Makkah, he entered from its higher side (a place now called al-Mu’alla gate) and went out from its lower side (now called Kuda).’ Agreed upon.
Grade:

Hadith #854 - Bulugh al-Maram (Bulugh al-Maram)
Whenever Ibn ‘Umar (RAA) came to Makkah he would spend the night at Dhi Tuwa valley (near Makkah), and in the morning he would bathe. ‘Ibn ‘Umar used to say that this is what the Messenger of Allah (ﷺ), used to do.’ Agreed upon.
Grade:

Hadith #855 - Bulugh al-Maram (Bulugh al-Maram)
Ibn ‘Abbas (RAA) narrated that he used to kiss the Black Stone and prostrate himself on it. Related by Al-Hakim and Al-Baihaqi.
Grade:

Hadith #856 - Bulugh al-Maram (Bulugh al-Maram)
Ibn ‘Abbas (RAA) narrated that the Messenger of Allah (ﷺ) commanded them to trot for three circuits and walk (with a normal pace) for four circuits, between the two corners (The Black Stone and the Yemeni corner). Agreed upon.
Grade:

Hadith #857 - Bulugh al-Maram (Bulugh al-Maram)
The Black Stone and the Yemeni corner) Related by Muslim.
Grade:

Hadith #858 - Bulugh al-Maram (Bulugh al-Maram)
‘Umar (RAA) narrated that he kissed the Black Stone and said, ‘I know that you are a stone and can neither benefit anyone nor harm anyone. Had I not seen Allah’s Messenger(ﷺ) kissing you, I would not have kissed you.’ Agreed upon.
Grade:

Hadith #859 - Bulugh al-Maram (Bulugh al-Maram)
Abu At-Tufail (RAA) narrated, ‘l saw Allah’s Messenger (ﷺ) making Tawaf round the Ka’bah and he was touching the corner (of the Black Stone) with a stick that he had with him and then kissing the stick.’ Related by Muslim.
Grade:

Hadith #860 - Bulugh al-Maram (Bulugh al-Maram)
Ya’li bin Umaiyah (RAA) narrated, The Messenger of Allah (ﷺ) made the Tawaf while wearing a green Yemeni mantle, bringing it up from under his right armpit while covering the left shoulder.’ Related by the five Imams except for An-Nasa’i. At-Tirmidhi graded it as Sahih
Grade:

Hadith #861 - Bulugh al-Maram (Bulugh al-Maram)
Anas (RAA) narrated, ‘When we assumed Ihram (for Hajj or ‘Umrah) some of us raised their voices with Talbiyah and nobody objected to that, and others raised their voices with Takbir and no one objected to that (which means that saying Allahu Akbar ‘Allah is the Greatest’, or reciting the Talbiyah are both acceptable during Ihram).’ Agreed upon.
Grade:

Hadith #862 - Bulugh al-Maram (Bulugh al-Maram)
Ibn ‘Abbas (RAA) narrated, ‘The Messenger of Allah (ﷺ) sent me at night from al-Muzdalifah (to Mina) with the weak members of his family (women and children).’ Agreed upon.
Grade:

Hadith #863 - Bulugh al-Maram (Bulugh al-Maram)
A’ishah (RAA) narrated, ‘Saudah(the wife of the Prophet (ﷺ) asked his permission, on the night of al-Muzdalifah, to leave earlier (to Mina as she was a heavy and slow woman.’ The Prophet (ﷺ) gave her permission.’ Agreed upon.
Grade:

Hadith #864 - Bulugh al-Maram (Bulugh al-Maram)
Ibn ‘Abbas (RAA) narrated, ‘The Messenger of Allah said to us, “Do not throw the pebbles at Jamrah al-‘Aqabah until sunrise.” Related by the five Imams except An-Nasa’i, but with a disconnected chain of narrators.
Grade:

Hadith #865 - Bulugh al-Maram (Bulugh al-Maram)
A’ishah (RAA) narrated, ‘The Prophet sent Umm Salamah on the night of the 10th (before the day of the Sacrifice) and she threw her pebbles before dawn, after which she returned to Makkah to perform Tawaf.’’ Related by Abu Dawud.
Grade:

Hadith #866 - Bulugh al-Maram (Bulugh al-Maram)
“Anyone who offered this prayer -at al-Muzdalifah- along with us, and waited with us until we returned to Mina, and he stayed at ‘Arafat (on the 9th ) before that by night or day, he would have completed the prescribed duties of Hajj.” Related by the five Imams. At-Tirmidhi and Ibn Khuzaimah graded it as Sahih.
Grade:

Hadith #867 - Bulugh al-Maram (Bulugh al-Maram)
‘Umar (RAA) narrated, ‘The pagans did not use to depart from Muzdalifah until the sun had risen, and they would say, ‘Let the sun shine on Thabir (the highest mountain in Makkah). The Messenger of Allah (ﷺ) contradicted them and departed from Muzdalifah before sunrise.’ Related by Al-Bukhari.
Grade:

Hadith #868 - Bulugh al-Maram (Bulugh al-Maram)
Ibn ‘Abbas and Usamah bin Zaid (RAA) narrated, The Messenger of Allah (ﷺ) kept on reciting Talbiyah until he threw the pebbles at Jamrat-ul ‘Aqabah..’ Related by Al-Bukhari.
Grade:

Hadith #869 - Bulugh al-Maram (Bulugh al-Maram)
‘Abdullah bin Masud (RAA) narrated that he kept the Ka’bah on his left and Mina on his right and threw the seven pebbles of Jamrat-ul ‘Aqabah. He then said, ‘This is the location where the one on whom surah al-Baqarah. (surah no. 2) was revealed (i e. the Messenger of Allah (ﷺ)).’ Agreed upon.
Grade:

Hadith #870 - Bulugh al-Maram (Bulugh al-Maram)
Jabir bin ‘Abdullah (RAA) narrated, ‘The Messenger of Allah (ﷺ) threw Jamrat—ul ‘Aqabah on the Day of Sacrifice (the 9th of Dhul Hijjah) in the forenoon. On the following days he threw them when the sun had passed its meridian.’ Related by Muslim.
Grade:

Hadith #871 - Bulugh al-Maram (Bulugh al-Maram)
Ibn ‘Umar (RAA) narrated that he used to throw the pebbles of al-Jamrat ud-Duniya (the Jamrah near to the Khaif mosque) with seven small pebbles, and would recite Takbir when throwing each pebble. Then he would go ahead until he reached the bottom of the valley, where he would stand for quite a long time facing the direction of the Qiblah, and raising his hands, while supplicating Allah. Then he went and threw seven pebbles at the second Jamrah(al-Jamarah al·Wosta) while saying Allahu Akbar w
Grade:

Hadith #872 - Bulugh al-Maram (Bulugh al-Maram)
“May Allah bless those who shaved.” The Companions asked him, ‘O Allah’s Messenger, what about those who cut their hair short?’ They repeated their question twice (and each time he repeated his saying, ‘May Allah bless those who shaved.’) On the third time, the Messenger of Allah (ﷺ) then said, “And (may Allah bless) those who cut their hair short.” Agreed upon.
Grade:

Hadith #873 - Bulugh al-Maram (Bulugh al-Maram)
“There is no harm, go and slaughter your animal.” Another man asked, ‘l slaughtered the animal before I threw the pebbles? Prophet (ﷺ) said: “There is no harm, go and throw your pebbles.” The narrator said: “Whoever asked the Prophet (ﷺ) about anything done before or after the other he told him “No harm done. Go and do (whatever you missed).” Agreed upon.
Grade:

Hadith #874 - Bulugh al-Maram (Bulugh al-Maram)
Al-Maisur bin Makhramah (RAA) narrated, ‘The Messenger of Allah (ﷺ) sacrificed his animal before he shaved and commanded his companions to do so.’ Related by Al-Bukhari.
Grade:

Hadith #875 - Bulugh al-Maram (Bulugh al-Maram)
“When one of you threw the pebbles and shaved his hair, everything including perfume becomes lawful for him except women (i.e. sexual intercourse).” Related by Ahmad and Abu Dawud with a weak chain of narrators.
Grade:

Hadith #876 - Bulugh al-Maram (Bulugh al-Maram)
“Women (pilgrims) do not have to shave (their heads); they may only shorten their hair.” Related by Abu Dawud with a good chain of narrators.
Grade:

Hadith #877 - Bulugh al-Maram (Bulugh al-Maram)
Ibn ‘Umar (RAA) narrated that ‘Al-’Abbas bin ‘Abdul Muttalib asked permission from the Prophet (ﷺ) to stay at Makkah during the nights of Mina in order to provide drinking water (from Zamzam) to the pilgrims, and the Prophet (ﷺ) allowed him.’ Agreed Upon.
Grade:

Hadith #878 - Bulugh al-Maram (Bulugh al-Maram)
‘Asim bin ‘Adi (RAA) narrated that the Messenger of Allah (ﷺ) excused the herdsmen of camels from sleeping at Mina and asked them to throw pebbles on the day of sacrifice (i.e. throw Jamrat-ul ‘Aqabah and they do not have to spend the night at Mina), and then to throw the pebbles of the next day and the day after (i.e. of the 11th and the 12th combined (on the 12th ), and then throw pebbles again on the 13th Related by the five Imams. At-Tirmidhi and Ibn Hibban graded it as Sahih.
Grade:

Hadith #879 - Bulugh al-Maram (Bulugh al-Maram)
Abu Bakrah (RAA) narrated that the Messenger of Allah (ﷺ) delivered a sermon to us on the Day of Nahr (sacrifice) (and the narrator mentioned the sermon.).’ Agreed upon.
Grade:

Hadith #880 - Bulugh al-Maram (Bulugh al-Maram)
Sarra’ bint Nabhan (RAA) narrated ‘The Messenger of Allah (ﷺ) delivered a sermon to us on the second day of sacrifice, ‘Yaum ar-Ru’us’ (11th of Dhul -Hijjah) and said, “Is this not the middle of the days of Tashriq?” Related by Abu Dawud.
Grade:

Hadith #881 - Bulugh al-Maram (Bulugh al-Maram)
A’ishah (RAA) narrated, ‘The Messenger of Allah (ﷺ) said to her, “Your Tawaf by the Ka’bah and your Sa’i between Safa and Marwah is sufficient for both your Hajj and ‘Umrah (i.e. one Tawaf and one Sa’i are sufficient as she combined Hajj and ‘Umrah.)’ Related by Muslim.
Grade:

Hadith #882 - Bulugh al-Maram (Bulugh al-Maram)
Ibn ‘Abbas (RAA) narrated that the Messenger of Allah (ﷺ) did not trot during the seven circuits made in the final Tawaf when he returned to Makkah.’ Related by the five Imams except at-Tirmidhi. Al-Hakim graded it as Sahih.
Grade:

Hadith #883 - Bulugh al-Maram (Bulugh al-Maram)
Anas (RAA), narrated, ‘The Messenger of Allah rested for a while at al-Muhassab (a valley opening at al-Abtah between Makkah and Mina) prayed Dhuhr, Asr, Maghrib and ‘Isha prayers after which he rode to the Ka’bah and made Tawaf.’ Related by Al·Bukhari.
Grade:

Hadith #884 - Bulugh al-Maram (Bulugh al-Maram)
A’ishah (RAA) narrated that she did not use to do that i.e. rest at al-Muhassab and said, ‘The Messenger of Allah (ﷺ) rested at al-Muhassab, because it was easier to stop there and depart from (i.e. it is not a Sunnah to rest there`). Related by Muslim.
Grade:

Hadith #885 - Bulugh al-Maram (Bulugh al-Maram)
Ibn ‘Abbas (RAA) narrated, ‘People were commanded to make the Tawaf round the Ka’bah their last rite;(Farewell Tawaf but the menstruating women were excused from it.’ Agreed upon.
Grade:

Hadith #886 - Bulugh al-Maram (Bulugh al-Maram)
“Offering prayer in my mosque (in Madinah) is better than one thousand prayers elsewhere, save for those offered prayer in al-Masjid al-Haram (in Makkah). And prayer offered in al-Masjid al-Haram is better than prayer offered in my mosque by one hundred prayers.” Related by Ahmad and Ibn Hibban graded it as Sahih.
Grade:

Hadith #887 - Bulugh al-Maram (Bulugh al-Maram)
Ibn ‘Abbas (RAA) narrated, ‘When the Prophet (ﷺ) was prevented from performing ‘Umrah (by Quraish) he shaved his head, had intercourse with his wives and slaughtered his animal. The next year he performed ‘Umrah to make up for the year that he had missed.’ Related by Al-Bukhari.
Grade:

Hadith #888 - Bulugh al-Maram (Bulugh al-Maram)
A’ishah (RAA) narrated, ‘The Messenger of Allah (ﷺ) went to visit. Duba’ah bint Az-Zubair bin ‘Abdul Muttalib. She said to him, ‘O Messenger of Allah I have made the intention to perform Hajj but I am suffering from an illness.’ He said to her, “Perform Hajj but set a condition that you shall be relieved of the Ihram whenever you are prevented (due to illness, etc.).” Agreed upon.
Grade:

Hadith #889 - Bulugh al-Maram (Bulugh al-Maram)
“If anyone breaks (a leg) or becomes lame (while he was performing Hajj or ‘Umrah) he is released from him Ihram and must perform Hajj the next year.’ ’lkrimah said, ‘l asked Ibn ‘Abbas and Abu Hurairah about this statement of Al-Hajjaj and they said that he had spoken the truth. Related by the five Imams. At-Tirmidhi graded it as Hasan.
Grade: